hi brainly user! ૮₍ ˃ ⤙ ˂ ₎ა
⊱┈────────────────────────┈⊰
[tex]\huge{ \rm{Answer:}}[/tex]
The roots of the equation are 7 and -4, because 7 - 4 = 3 and 7. - 4 = -28
Step-by-step explanation:
The positive number is equal to 7.
Assuming that the number is equal to "x" we have:
[tex]\begin{gathered}x^2 = 3x + 28\\\\x^2 - 3x - 28 = 0\\\\a = 1\\\\b = -3\\\\c = -28\\\end{gathered}[/tex]
By the sum and product method, we have:
[tex]\begin{gathered}S = -b / a\\\\S = -(-3) / 1\\\\S = 3\\\\\end{gathered}[/tex]
[tex]\begin{gathered}P= c / a\\\\P = 28 / 1\\\\P = 28\\\\\end{gathered}[/tex]